Liquid-phase exfoliated graphene-MoS2 based saturable absorber for Q-switched Erbium Doped fiber laser - Halim, S. N. M.; Jasni, Nur Afiqah Husna; Mohamad Taib, Mohamad Fariz; Wan Nawawi, Wan Mohd Fazli; Ahmad, Fauzan (IOP Publishing, 2021)
Upon exfoliation from the bulk form, two-dimensional materials have shown ubiquitous properties which are suitable for Q-switched pulsed laser generation. In this research, a successful solution process of graphene-MoS2 nanocomposite saturable absorber through liquid phase exfoliation has been carried out. The method offers a low-cost route for simple and scalable production while providing a promising material quality with on-demand properties and integration flexibility. Stable Q-switched laser operation was realized with graphene-MoS2 hybrid saturable absorber. The pulse duration was measured to be 6 µs with repetition rate of 63.92 kHz corresponding to a peak power and pulse energy of 5.05 mW and 30.87 nJ, respectively.